(3ejRGf GdbjGeIs - (3GdcGTj Ch GdcGTGfj, , GdajV, eMeO Hf eQJVi Hf eMehO, J (B1091(3g`s ((3GdfLas)
(3ChdgG (B:s
(3GdMeO ddg GdPj QaY GdSeGA hhhVY GdejRGf(B... (3hHYO(B... (3gPG eG CdgeJ Hg aj JMbjb ejRGf GdbjGeI jhe GdbjGeI Ydi efgL GdbSW hWQjb GdGSJbGeI(B...s
(3BNQgG (B:s
(3hGdHGH GdSGOS GdeTJed Ydi eG jhRf hjDcOg hjhVMg(B... (3eG jMbb GdTjA hHGSe Pdc GdTjA hEPG hajfG HeG hYOfG adfbHV YfGf Gdbdes
(3JHUQI GdeDda (B:s
(3haj GSeg NdGa(B: (3eMSf Hf eQJVi, Ch eMSf Hf eMeO, Ch eMeO eMSfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B617s
(3GdCYdGe(B: (3L(B5(3, U(B290s
(3gOjI GdYGQajf(B: (3L(B2(3, U(B7s
Keywords: (3GdJhMjO hGdedd hGdfMds